Migration and Alignment of Three Interacting Particles in Poiseuille Flow of Giesekus Fluids - Bing-Rui Liu (Fluids, 2021)
Effect of rheological property on the migration and alignment of three interacting particles in Poiseuille flow of Giesekus fluids is studied with the direct-forcing fictitious domain method for the Weissenberg number (Wi) ranging from 0.1 to 1.5, the mobility parameter ranging from 0.1 to 0.7, the ratio of particle diameter to channel height ranging from 0.2 to 0.4, the ratio of the solvent viscosity to the total viscosity being 0.3 and the initial distance (y0) of particles from the centerline ranging from 0 to 0.2. The results showed that the effect of y0 on the migration and alignment of particles is significant. The variation of off-centerline (y0 ≠ 0) particle spacing is completely different from that of on-centerline (y0 = 0) particle spacing. As the initial vertical distance y0 increased, the various types of particle spacing are more diversified. For the off-centerline particle, the change of particle spacing is mainly concentrated in the process of cross-flow migration. Additionally, the polymer extension is proportional to both the Weissenberg number and confinement ratio. The bigger the Wi and confinement ratio is, the bigger the increment of spacing is. The memory of shear-thinning is responsible for the reduction of d1. Furthermore, the particles migrate abnormally due to the interparticle interaction.